N032 Impact of pain due to subcutaneous administration of a biological drug. (16th January 2018) - Gely, C; Marin, L; Gordillo, J; Mañosa, M; Bertoletti, F; Cañete, F; Gonzalez-Muñosa, C; Cabré, E; Domènech, E; Garcia-Planella, E
Abstract: Background: Adalimumab is a monoclonal antibody that is injected subcutaneously and it is widely used in inflammatory bowel disease. Subcutaneous administration represents an advantage in relation to patient's autonomy but does not provide direct monitoring of adherence. The excipients of subcutaneous drugs can cause pain in the injection site and their impact on patient's perception and its consequences has been scarcely assessed. The aim of this study was to assess the impact of the presence or absence of pain related to the subcutaneous administration of adalimumab. Methods: Patients with Crohn's disease (CD) and ulcerative colitis (UC) who were on adalimumab treatment within the last 12 months in two referral hospitals, were invited to participate in an anonymous survey with a structured questionnaire to evaluate the impact of citrate withdrawal as excipient of adalimumab injections. Pain due to subcutaneous administration of adalimumab was evaluated through a visual analogue scale (1–10). Results: Fifty-six surveys were obtained (51 CD, 5 UC). Among the participants, 70% women, 28% active smokers, 44% have secondary education and 34% have university degrees. Median age at the beginning of the adalimumab was 47 years (IQR 33–59). The date of adalimumab beginning ranged from 2006 to 2016. 80% of patients received adalimumab eow and 20% weekly, for the last 6 months. In 80% of patients adalimumab was self-administered. 25% of the patients were previously experienced with subcutaneous drugs. 77% of the patients reported having suffered pain at some time, with a mean pain intensity of 5.9 ± 2.5. 33% of the patients considered that pain affected their adherence to treatment, with 79% of them causing pre-administration anxiety. 83% of the patients recognised a change in the perception of pain with citrate-free administration; only 4% remained with the perception of pain with an average intensity of 3.2 ± 1.7. The citrate-free presentation was considered a very positive change (mean of 8.1 ± 1.9 out of 10) with the disappearance of pre-administration anxiety and improvement in adherence. Conclusions: Conclusions: Pain as a side effect of subcutaneous drugs is underestimated. It may decrease adherence and impact the patients' quality of life due to the anxiety.